Tailoring compliance risk and the compliance function for non-financial organizations: A step further and beyond the Basel's proposels for banks - Rodolfo Apreda (Universidad del Centro de Estudios Macroeconómicos de Argentina (UCEMA), 2006)
This paper contends that compliance risk and the compliance function are powerful devices to enhance corporate governance not only in banks but in any other organization as well. Firstly, it reviews the contribution made by the Bank for International Settlements (BIS), which pertains to financial institutions only. Next, it upholds that compliance risk actually matters in any corporate governance environment. Afterwards, it deals with how the compliance function can be shaped so as to grant, on the one hand, its own independence and, on the other, clear-cut patterns of accountability behavior. Subsequently, it points out that there are some drawbacks in the BIS'choice of governance principles. Lastly, it brings forth a set of governance principles for both compliance risk and the compliance function in financial and non-financial organizations alike.
Keywords: G30; G34; G38; 330; compliance risk; compliance function; accountability; corporate governance; banks governance; accountability